The top 100 most cited papers on endometrial carcinoma: A bibliometric analysis - Xiao, Peichen; Yao, Chenchen; Wang, Guangxin (Frontiers in Oncology, 2022)
Objective: This study aimed to analyze the top 100 most cited papers and research trends on endometrial carcinoma via bibliometric methods. Methods: On the 1st of March 2022, the top 100 most cited papers regarding endometrial carcinoma published from 1971 to 2021 were identified through searching Web of Science Core Collection database and the following data: title, author, journal, publication year, country and institution were extracted. Microsoft Office Excel (2019) was used for descriptive statistical analysis. VOSviewer (1.6.18) was used to perform and visualize co-authorship analysis and co-occurrence analysis. Results: These 100 papers were cited a total of 45, 685 times, and the mean number of citations was 456.85 (range, 228 to 2487). Most papers were published between 1996 and 2000, and between 2006 and 2010. The Lancet published the largest number of papers (n=12), followed by Gynecologic Oncology (n=11). Most of the papers were from the United States (n=58), followed by Italy (n=8) and Netherlands (n=7). Duke University, Johns Hopkins University, University of California San Francisco and University of Southern California (all in United States) contributed the most papers (n=4, respectively). Nicoletta Colombo contributed the most papers (n=3) as the corresponding author. The co-occurrence keywords were classified into three clusters: cluster 1 (epidemiology study), cluster 2 (molecular biology study) and cluster 3 (clinical treatment study). Early research that was published prior to 2005 in this field was mainly focused on epidemiology and molecular biology; the mean publication year for keywords in cluster 3 was later than other clusters. The keywords “external-beam radiotherapy,” “uterine serous carcinoma,” and “intermediate-risk” showed relatively later mean publication year and lower mean frequency of occurrence. Conclusions: This study provides medical researchers with bibliometric information relating to endometrial carcinoma. Our results show that the United States is a clear leader in this field. The clinical treatment of endometrial carcinoma has received increasing levels of attention over recent years and is likely to remain a major area of research in the future. Meanwhile, it is recommended to pay attention to potential research hotspots, such as external-beam radiotherapy, uterine serous carcinoma and intermediate-risk.